Pendekatan Terpadu dalam Membentuk Karakter Santri di Pondok Pesantren Sabilul Hasanah Banyuasin III - Zuhdiyah Zuhdiyah (Intizar, 2013)
Pendidikan karakter adalah sistem penanaman nilai-nilai karakter kepada peserta didik yang mencakup komponen, kesadaran, pemahaman, kepedulian, dan komitmen untuk melaksanakan nilai-nilai tersebut baik kepada Allah, diri kita sendiri, orang lain, lingkungan, atau masyarakat dan bangsa secara keseluruhan. Penelitian ini menggunakan dua jenis data adalah jenis data primer dan data sekunder. data primer. Dari pengamatan di atas, diketahui bahwa waktu penerimaan terhadap calon santri dibakukan kriteria, tes seleksi bahan yang dapat menentukan kelulusan siswa, dan jumlah peminat ke pondok pesantren Sabilul Hasanah pada 5 (lima) tahun peningkatan atau meningkat dari tahun-tahun sebelumnya. Begitu pun dengan masa orientasi waktu sementara telah distandarisasi bahan orientasi pondok dapat mempersiapkan anak-anak belajar di pondok, dan ruang belajar di mana siswa dan mahasiswa laki-laki terpisah perempuan sebahagian terutama untuk Madrasah Diniyyah. Pendekatan terpadu yang diterapkan di pesantren Sabilul Hasanah adalah pendekatan eksperimen. Para siswa memperoleh pengalaman melalui berbagai kegiatan yang dilakukan di sekolah-sekolah. Siswa juga mendapatkan pengalaman dalam kegiatan sehari-hari mereka, dan belajar untuk mandiri, dan bertanggung jawab untuk diri mereka sendiri, pendekatan pembiasaan.Character education is a system of cultivation of character values to learners that includes components, awareness, understanding, caring, and commitment to implement these values, both to Allah, ourselves, others, the environment, or society and the nation as a whole, so that a perfect human being in accordance with nature. This study uses two types of data are the type of primary data and secondary data. Primary data, according to Muri Yusuf (1997, p. 25) is "data collected by the person / agency / researcher from the first source". This means that the primary data obtained directly by the researcher from the original source. Average secondary data, according to Muri Yusuf (1997, p. 25) is "data collected by the person / agency / other researchers". From the observations above, it is known that the time of acceptance of the prospective students have standardized criteria for prospective students female students who received has been set, material selection test prospective students measurable benchmarks graduation of students who received accurate, and the number of enthusiasts into the cottage Sabilul Hasanah Islamic boarding cshool in 5 (five) years an increase or an increase from previous years are refresentatif. So even with an orientation period of time while the cabin has been standardized materials orientation of the lodge can prepare children learn in the cottage, and a study room where female students and students of separate men sebahagian especially for Madrasah Diniyyah. The integrated approach that applied in Sabilul Hasanah Islamic boarding cshool is the the Experience Approach. The students gain experience through a variety of activities carried out in schools Pupils also gain experience in their daily activities, and learn to be independent, and is responsible for themselves, approach habituation.